The economic characteristics of small business development ( on the materials of the East - Kazakhstan region ) . (Journal of Economic Research & Business Administration, 2015)
In Kazakhstan the economy transformation conditions, small business plays a very important role in the local economy , as well as across the country , as in fact established territorial specialization of small businesses allowed him to complement the "big" the economy and form a relatively complete , integrated structure of the economy of regions, cities and rural areas.
Keywords: Economic characteristics of the development; small business